Association Between Mean Platelet Volume (MPV) with Major Adverse Cardiovascular Events in Acute Coronary Syndrome during Hospitalization - Hasanah Mumpuni; Hariadi Hariawan; Lucia Kris Dinarti (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2016)
Background: Platelets play a central role in the pathogenesis of acute coronary syndrome with various clinical manifestations of unstable angina pectoris, myocardial infarction with ST segment elevation, and myocardial infarction without ST segment elevation. Mean platelet volume (MPV), the average size of platelets in blood obtained from routine blood tests, reflects the activation of platelets. Previous study revealed that higher MPV showed a higher thrombotic potential, by increasing the platelet activation, secretion of tromboxan A2 and the expression of glycoprotein Ib and IIb/IIIa receptors. This study aims to determine whether the MPV may predict the major cardiovascular events in patients with acute coronary syndrome.Metode: We perform a retrospective cohort study involving 372 patients with acute coroanry syndrome who admitted to Intensive Cardiac Care Unit Dr. Sardjito Hospital Yogyakarta. The research is conducted between January 2009 to January 2011, comprising 180 (48.3%) STEMI patients, 87 (23.3%)NSTEMI patients and 105 (28.4%) unastable angina patients. Subjects are further grouped as those with high MPV and low MPV. MPV measurement is obtained on routine blood tests of those patients.The major adverse cardiovascular events are cardiovascular death, non fatal reinfarction, stroke, acute heart failure and cardiogenic shock.Result: Cut-off value of MPV in this study is 8.85 fL determined with ROC curve analysis. The major adverse cardiovascular events is significantly higher in those with MPV >8.85 fL compared with those with the MPV ≤8.85 fL (incidence: 28.4% vs. 18.9%, p = 0.034), with the relative risk (RR) 1.65, 95% CI 1.037-2.783. The mean MPV in patients with major adverse cardiovascular events was significantly higher as compared to those without major adverse cardiovascular events (9.506 ± 1.76 fl vs.8.96 ± 1.45 fl, p = 0.001).Conclusion: Mean platelet volume (MPV) are associated with major adverse cardiovascular events in acute coronary syndrome. The high MPV may be considered as a predictor of major cardiovascular events in patients with acute coronary syndrome.Keywords: acute coronary syndrome, mean platelet volume, major adverse cardiovascular events.